Pengelolaan Terbitan Berkala Ilmiah Sesuai Ketentuan Akreditasi: Upaya Menuju Jurnal Trakreditasi Dan Bereputasi Internasional - Wahid Nashihuddin; Dwi Ridho Aulianto (Jurnal Pustakawan Indonesia, 2016)
Journal accreditation program aims to improve the quality and quantity of publications in the scientific community so as to competitiveness on the international scientific periodicals. This study aims to: (1) describe the journals that have been accredited by LIPI and Higher Education, which is viewed from the aspect field of science, the agency issuing, and the city of an issue; and 2) know the effort in preparing for publication journal managers become accredited and reputable international journals. Data sourced from literature studies, in the form of regulatory documents, articles, papers and presentations related to the accreditation of scientific periodicals. The data were analyzed descriptively. The conclusion of this study, namely: (1) 362 accredited journals, from LIPI total of 190 journals and 172 journals a number of Higher Education; the number of accredited journals is considered still relatively very small (only about 5.17%) when compared to the total number of indexed journals Indonesia ISJD (about 7000 journals); (2) accredited journals LIPI and DIKTI mostly from the city of Jakarta (of 113 journals, or 31.22%) to the science of Agriculture Veterinary Medicine and the Environment (43 accredited journals LIPI) and the health sector (34 accredited journal Higher Education); (3) the agency issuing the journal mostly from ministries agencies (134 journals or 70.53%) and university (99 journals or 57.56%); and (4) journal managers should immediately publish the journal in electronic version by paying attention to scientific principles in order to get the title of accredited and reputable international journals.Keywoords : Journal, Journal acreditation, International Journal, Open Jounrnal System, LIPI, DIKTI